Boundary Work in Response to Professionals' Contextual Constraints: Micro-strategies in Interprofessional Collaboration. Issue 9 (September 2022) - Weber, Clarissa E.; Kortkamp, Christian; Maurer, Indre; Hummers, Eva
Boundary-work research has extensively explored how professionals engage in boundary work to protect or expand their professional boundaries in interprofessional collaboration (IPC). Yet professionals' contextual constraints in everyday work, such as time pressure or legal restrictions, often result in competing interests of the professionals involved in IPC, prompting them to engage in boundary work to limit—instead of protect or expand—their boundaries. Our empirical analysis uses comprehensive qualitative data on IPC in Germany between self-employed general practitioners (GPs) and registered nurses employed in nursing homes. In this IPC, GPs' efficiency interests frequently compete with nurses' safeguarding interests, leading both professionals to engage in boundary-work efforts to limit their boundaries. Our findings provide a comprehensive understanding and framework of professionals' boundary work, showing that individual GPs and nurses typically hold a portfolio of various defending and accommodating micro-strategies. Based on our first-order findings, we identify how different sources of power enable particular micro-strategies and explore how the choice of micro-strategies depends on different forms of trust in the collaborating partner. Last, we outline interactions of micro-strategies, illustrating how the outcomes of professionals' bilateral boundary work depend on the sequence of these strategies.